Kwalifikacje i kompetencje trenerów personalnych a oczekiwania rynku pracy = Personal trainers professional qualifications - demands of the labour market - Leśniewska, Aleksandra; Stosik, Aneta (Journal of Education, Health and Sport, 2016)
Leśniewska Aleksandra, Stosik Aneta. Kwalifikacje i kompetencje trenerów personalnych a oczekiwania rynku pracy = Personal trainers professional qualifications - demands of the labour market. Journal of Education, Health and Sport. 2016;6(9):25-35. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61707 http://www.ojs.ukw.edu.pl/index.php/johs/article/view/3831 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Pola nd Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Streszczenie Rynek usług fitness w Polsce nieustannie i dynamicznie się rozwija. Kluby fitness oferują obecnie swoim klientom szeroką gamę usług, od zorganizowanych zajęć grupowych po indywidualne formy treningowe, takie jak trening personalny, który cieszy się coraz większym zainteresowaniem. Jednak trenerzy personalni, mimo tak sprzyjających trendów rynkowych, borykają się aktualnie z problemem braku standardów kwalifikacji zawodowych oraz niespójnym systemem kształcenia w Polsce. Celem artykułu była analiza oczekiwań kwalifikacji i kompetencji trenerów personalnych z perspektywy wymagań rynku pracy – czyli oczekiwań pracodawców prowadzących rekrutacje w swoich organizacjach. Słowa kluczowe: trener personalny, usługi fitness, kwalifikacje i kompetencje, rynek pracy Abstract Fitness has been a growth industry over the past years and seems not to be saturated on the polish ground. Fitness clubs offer a wide range of services to their clients from group classes to individual trainings such as personal training. However, personal trainers in Poland have conducive and effortless way to access to their profession, they still struggle with the lack of professional standards and incoherent educationa; system. The main purpose of this article was to define what are the demands of the labour market in terms of required qualifications and competences for personal trainers who are taking part in recruitment process. Keywords: personal trainer, fitness services, qualifications and competencies, labour market